Households of St Edmund. (4th January 2016) - Foot, Sarah
Abstract : Theodred, bishop of London, who also held episcopal authority in Suffolk and Norfolk, drew up a statement in the 940s of how he intended to leave his property after his death. Despite his German name, he was probably a native of Suffolk, for he bequeathed a number of Suffolk lands to close relatives living in the region. His most generous bequests were to his cathedral church of St Paul in London, but he made a substantial grant of four estates in Suffolk to the church of St Edmund. Theodred's will provides one of the earliest datable references to the existence of a religious household charged with maintaining the cult of St Edmund. King of the East Angles, Edmund had died in 869, having been defeated in battle by a Danish army which went on to conquer his kingdom. Later generations remembered him as a martyr, although contemporary sources said little about the circumstances of his death. A community of St Edmund was well established at Bury by the middle years of the tenth century, inspiring not only the generosity of the local bishop, but also his confidence in the efficacy of the congregation's prayers. Theodred bequeathed land to the church of St Edmund as the property of God's community there, for the good of his own soul. Exactly when a religious congregation first assembled to preserve the memory of the martyred king, and when it erected a wooden church to house his shrine remains, however, debatable.